Mengembangkan Kreativitas Anak Usia Dini Melalui Strategi 4P (Pribadi, Pendorong, Proses, Produk) - Rahimah, Rahimah (Pusat Studi Pendidikan Kreatifitas Anak Wadas Kelir Purwokerto, 2019)
In connection with the development of student creativity, we need to review fouraspects of creativity, namely personal, driving, process, and product (4P of creativity).This unique person can be expected to arise. From this unique personal expression canbe expected the emergence of new ideas and innovative products. Therefore educationshould be able to appreciate the personal uniqueness and talents of their students, theteacher should help his students find their talents and appreciate them. Students'creative talent will be realized if there is encouragement and support from theirenvironment, or if there is a strong urge in themselves (internal motivation) to producesomething. To develop creatively, children need to be given the opportunity to activelyengage themselves. Educators should be able to stimulate themselves to engage increative activities, by helping to work out the necessary facilities and infrastructure. Thisstudy aims to develop children's creativity and can be developed optimally, because it isone indicator of the success of education that is able to carry out one of its tasks, namelycreating people who are able to do something new, not only repeat what the previousgeneration has done . They are creative people, finding something that has neverexisted or combining something that already exists becomes new.